Traditional processing and utilization of cassava in Africa: IITA research guide, No. 41 - Hahn, S.K. (1997)
Cassava is playing a major role in African food systems. Processing of cassava has several objectives and advantages. Traditionally, cassava is processed into many products. However, several constraints affect cassava processing. Cyanide content in the roots is a major limitation of cassava utilization, but can be reduced by appropriate processing. Traditional processing does not require sophisticated equipment, but storage requirement of the processed products are critical. At many locations, cassava leaves are used as a preferred green vegetable. Future research on improved cassava processing and utilization techniques would greatly increase labour efficiency, productivity and nutrition.